Friends Without Benefits? New EMU Members and the "Euro Effect" on Trade - Alina Mika; Robert Zymek (Center for Economic Studies and ifo Institute (CESifo), 2017)
We re-visit the evidence about the trade benefits of European Monetary Union (EMU), focusing on the experience of countries which adopted the common currency since 2002. Based on “state of the art” gravity estimations for the period 1992-2013, we reach three main conclusions. First, estimates from an appropriately specified and estimated gravity equation provide no evidence of a euro effect on trade flows among early euro adopters up to the year 2002. Second, this finding is robust to extending the sample period to incorporate data up to 2013, covering five additional euro accessions. Third, while there is no robust evidence of a euro effect, there is evidence that intra-EU trade flows have expanded faster than the global average during the 2002-2013 period. Using the functional form of a theory-consistent gravity equation, we perform pseudo out-of-sample forecasts of trade flows for recent euro joiners. In line with our estimation results, we show that pseudo forecasts of the change in trade flows after euro accession, assuming no euro effect, outperform forecasts based on the expectation of a significantly positive effect. This suggests that euro accession countries should not expect a significant boost to their trade from joining EMU.
Keywords: F14; F15; F17; F33; 330; euro; trade; gravity; poisson